
Not finding help here? Sign up for a free 30min tutor trial with Chegg TutorsDismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!
Proof that LCM(c,d) divides LCM(a,b), known GCD(a,b) divides GCD(c,d)
 Similar Discussions: Proof that LCM(c,d) divides LCM(a,b), known GCD(a,b) divides GCD(c,d)

Solve ab=gcd(a,b)*lcm(a,b) (Replies: 3)

If lcm(a,b) = ab, why is gcd(a,b) = 1? (Replies: 4)

Gcd(a, b, c) = gcd(gcd(a,b), c) (Replies: 2)

Number Theory. If d=gcd(a,b) then (Replies: 1)
Loading...